IMPLEMENTASI METODE SAW DALAM MENENTUKAN SITUS E-COMMERCE TERBAIK DI KEL TANAH TINGGI KEC JOHAR BARU JAKARTA PUSAT - Lutfi Karim; Frencis Matheos Sarimole (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
The rapid progress of the business world has transformed from traditional to digital, this is something that is the basis for the emergence of the e-commerce industry in this era as an effort to bridge between consumers and sellers in order to exchange goods and money. The development of the world of e-commerce locally and externally is considered very fast, this is triggered by increased sales through electronic media, so that competition becomes more competitive. Therefore, we need to know the reasons why consumers choose to shop at certain e-commerce companies, and what is behind consumers in choosing these e-commerce sites. This article discusses the results of the calculation of a decision support system using the Simple Additive Weighting method where the criteria are predetermined to choose one of the best e-commerce sites in one of the Kelurahan in Central Jakarta.